Evaluación de dos métodos alternativos de propagación de tres variedades de flores tropicales heliconias - Pérez Añazco, Sheyler Vladimir (2011)
In the Farm Santa Inés of the Ability of Agricultural Sciences of the Technical University you development the relative investigation to "propagation of three varieties of Heliconias disinfected in solutions of chlorine and planted in three sustratos. The outlined objectives were: To evaluate two alternative methods of propagation of tropical flowers and to determine which of the two substrates (sand and earth) it is better to obtain the best percentage of capable plants for the sowing or I transplanted definitive. The study includes three rooting substrates and initial growth of three varieties of Heliconias, Conoide, Rostrata and Musoide. The substrates combined with the disinfection of the vegetable material by means of immersion in a solution of chlorine 75 % - immersion 20 minutes, solution of chlorine to 50 % for 40 minutes, conforming 9 combinations or treatments. The treatments were assigned to plastic cases integrating a Factorial experiment, included in the Design Randomizado it Supplements with three repetitions. They were carried out the measurement of the evaluated following variables they were: sprouting percentage to the 30 and 45 days, the height of plants and number of leaves to the 45 days, the percentage of living roots and of plants spread to the 60 days. The varieties of exposed heliconias at different times of disinfection in solutions of chlorine to the 75 and 50 %, and sowed in substrates of sand and agricultural floor, they fastened 100 % of the plants and they reached the best averages in plant height the 45 days, of the roots.